Analisis Personalisasi Partai Politik di Era Reformasi - Definitif Mendrofa; Efriza Efriza (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2022)
Political parties must become accountable democratic institutions, but many parties are mired in personalized management. the impact of party personalization in the reform era. Method The research objective is expected to contribute to the understanding of the research used, namely library research. From the results of this study, the reality is that political parties in Indonesia tend to be in a personalization situation, in the form of a very central figure who becomes a determinant for the party. Therefore, the existence of this figure will lead to a very strong dependence of the party on the central figure.